2005
DOI: 10.1081/jfp-200060239
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological Characteristics of Part-Baked White Pan Bread During Storage

Abstract: In this study, white pan breads part-baked 10, 15, and 20 min with and without added calcium propionate were stored at 20 C (room temperature) for 3, 5, and 7 days and at 4°C (refrigerator temperature) for 7, 14, and 21 days. After storage, the baking time of part-baked breads was completed to the baking time of control breads (25 min). Total aerobic mesophylic bacteria (TAMB), coliform bacteria, yeast and mold, and Bacillus spore counts of breads were determined before and after the second baking. While TAMB,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 9 publications
1
19
1
1
Order By: Relevance
“…Bacillus from part-baked Irish brown soda bread stored at 20°C did not show growth in conventional microbiological medium (pH 10) at 4°C (Leuschner et al, 1998). On the other hand, Karaoglu et al (2005) showed microbial counts from part-baked bread stored at 4°C 0260-8774/$ -see front matter Ó 2008 Elsevier Ltd. All rights reserved. doi:10.1016/j.jfoodeng.2008.05.020 lower than those from bread stored at ambient temperature.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Bacillus from part-baked Irish brown soda bread stored at 20°C did not show growth in conventional microbiological medium (pH 10) at 4°C (Leuschner et al, 1998). On the other hand, Karaoglu et al (2005) showed microbial counts from part-baked bread stored at 4°C 0260-8774/$ -see front matter Ó 2008 Elsevier Ltd. All rights reserved. doi:10.1016/j.jfoodeng.2008.05.020 lower than those from bread stored at ambient temperature.…”
Section: Introductionmentioning
confidence: 89%
“…Because of that, extensive research has been conducted in part-baked bread. Some of these studies in part-baked bread are related with sensorial and textural characteristics (Carr et al, 2006;Fik and Surowka, 2002); microbial quality (Leuschner et al, 1998(Leuschner et al, , 1999Karaoglu et al, 2005); the use of hydrocolloids as antistaling agents Rosell, 2006, 2007;Bárcenas et al, 2004a); physical changes related with pre-chilling and freezing processes (Le Bail et al, 2005;Lucas et al, 2005a,b;Ribotta and Le Bail, 2007); changes during storage at refrigerated conditions Rosell, 2006, 2007;Karaoglu, 2006a,b;Leuschner et al, 1997Leuschner et al, , 1999; and others related with moisture diffusivity and water activity (Hamdami et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Serial decimal dilutions were made using 0.1% peptone solution. Total aerobic mesophylic bacteria count was determined on plate count agar medium (Karaoglu et al, 2005) after incubation at 30 C for 72 h. Yeasts and moulds were determined on plates with Sabouraud agar medium, incubated at 25 C for 3e5 days (Odds, 1991). The levels of vegetative and spore-forming amylolytic aerobic bacteria were assayed on agar medium with starch, according to Waksman (Polish Standard PN-A-74134-4, 1998).…”
Section: Microbiological Analysesmentioning
confidence: 99%
“…Pichia anomala, Hyphopichia burtonii and Saccharomycopsis fi buligera are spoilage yeasts causing chalk mould defects on part baked breads. A study carried out by Karaoglu et al ( 2005 ) showed that microorganism counts increased signifi cantly when part baked breads were stored at 20 °C (room temperature) for 3, 5, and 7 days, and the second baking contributed to the re-freshness of breads and decreased the microorganism counts. The levels of water activity for full baked breads (ranged from 0.92 to 0.89) did not signifi cantly affect the microorganism counts.…”
Section: Physico-chemical Changes During Storagementioning
confidence: 99%
“…The levels of water activity for full baked breads (ranged from 0.92 to 0.89) did not signifi cantly affect the microorganism counts. However, addition of calcium propionate in the bread formulation signifi cantly decreased total aerobic mesophylic bacteria, coliform bacteria, Bacillus spore, yeast and mould counts, although the extent of reduction depended on the pH levels (Karaoglu et al 2005 ).…”
Section: Physico-chemical Changes During Storagementioning
confidence: 99%